Impacts of turbidity on an epibiotic ciliate in the St Lucia Estuary, South Africa - Salome Jones; Nicola K. Carrasco; Andre Vosloo; Renzo Perissinotto (Hydrobiologia, 2018)

Abalone growth and associated aspects: now from a metabolic perspective - Leonie Venter; Du Toit Loots; Andre Vosloo; Peet Jansen van Rensburg; Jeremie Zander Lindeque (Reviews in Aquaculture, 2018)
Worldwide, there are approximately 100 Haliotis species, more commonly known as abalone or ‘Paua’ in New Zealand, ‘Venus's‐ears’ in Greece, ‘Awabi’ in Japan, ‘Perlemoen’ in South Africa and ‘Ormers’ in Europe. Regardless of what they are called in any part of the world, a high monetary value is coupled to this animal, because it is largely considered a seafood delicacy. Subsequently, a great deal of research primarily focused on improving the health and growth rates of abalone were carried out to maximise productivity of the commercial farming efforts in various countries. In this review, we comprehensively describe the most recent available scientific literature on abalone biology, and those aspects related to the growth of this organism; more specifically, those factors related to the uptake and breakdown of metabolic products which ensures long‐term growth. We subsequently discuss this in terms of basic animal design, farming outcomes, feeding, cellular growth mechanisms and the unique metabolic processes that exist in these species. Using this information and the knowledge of the metabolic processes in other organisms, we additionally make a number of new hypotheses regarding how these metabolic processes may function in terms of abalone growth. Based on the information presented in this review, we also identify major research opportunities and gaps in the existing knowledge of abalone metabolism, which when elucidated may not only serve the purpose of better understanding these organisms growth but also could potentially lead to increased productivity of the abalone commercial farming sector.

Possible maternal offloading of metals in the plasma, uterine and capsule fluid of pregnant ragged-tooth sharks (Carcharias taurus) on the east coast of South Africa - Kristina Naidoo; Anil Chuturgoon; Geremy Cliff; Sanil Singh; Megan Ellis; Nicholas Otway; Andre Vosloo; Michael Gregory (Environmental Science and Pollution Research, 2017)

Impact of a flood event on the zooplankton of an estuarine lake - Salome Jones; Renzo Perissinotto; Nicola Kim Carrasco; Andre Vosloo (Marine Biology Research, 2016)

Can diatom-based pollution indices be used for biomonitoring in South Africa? A case study of the Crocodile West and Marico water management area - Jonathan Charles Taylor; Jean Prygiel; Andre Vosloo; Pieter A. de la Rey; Leon van Rensburg (Hydrobiologia, 2007)